Provenance informing restitution: the case of Isleta paintings - Botticelli, Peter (Archival science, 2025)
This work presents a case study that examines a complex web of cultural documentation that spans multiple record formats and creators with varying, and sometimes conflicting, perspectives. We show how recent efforts to expand and refine the archival concept of provenance may carry practical benefits for a broad range of cultural heritage professionals as they seek to organize and interpret collections that cut across distinct personal, social, institutional, and disciplinary boundaries. The case explores provenance as an interdisciplinary framework that might be applied by archives, museums, and libraries as a means to inform restitution for cultural heritage representing non-Western cultures. The case shows how an archival approach to provenance research can be an effective means through which cultural heritage professionals may evaluate the actions and underlying perspectives of record creators and subjects, hopefully leading to richer, more complete accounts of how objects have been collected by individuals as well as the communities to which they belong.